Unified Smith predictor based H∞ wide-Area damping controller to improve the control resiliency to communication failure - Sarkar M.; Subudhi B.; Ghosh S. (My University, 2025)
Inter-Area low frequency oscillation in power system is one of the major problems for bulk power transmission through weak tie lines. Use of wide-Area signal is more effective than the local area signal in damping out the inter-Area oscillations. Wide area measurement system WAMS is convenient to transmit the wide area signal through the communication channel to the remote location. Communication failure is one of the disastrous phenomena in a communication channel. In this paper, a dual input single output DISO H∞ controller is designed to build the control resiliency by employing two highest observability ranking wide area signals with respect to the critical damping inter-Area mode. The proposed controller can provide sufficient damping to the system and also the system remains stabilized if one of the wide-Area signals is lost. The time delay is an unwanted phenomenon that degrades the performance of the controllers. The unified Smith predictor approach is used to design a H∞ controller to handle the time delay. Kundurs two-Area and IEEE-39 bus test systems are considered to verify the effectiveness of the proposed controller. From the simulation results, it is verified that, the proposed controller provides excellent damping performance at normal communication and improves the controller resiliency to counteract the communication failure. © 2014 Chinese Association of Automation.